Comparing severe injuries by sex and sport in collegiate-level athletes: a descriptive epidemiologic study - Hurtubise, J. M.; Beech, C.; Macpherson, A. (International Journal of Athletic Therapy & Training, 2015)
Context: There is a lack of research on sex differences for severe injuries across a variety of sports at the collegiate level.